Withdrawal from familial ovarian cancer screening for surgery: findings from a psychological evaluation study (PsyFOCS). - Lifford, K; Fraser, L; Rosenthal, A; Rogers, M; Lancastle, D; Phelps, C; Watson, E; Clements, A; Iredale, R; Jacobs, I; Menon, U; Brain, K (2012)
OBJECTIVE: A prospective psychological evaluation study of familial ovarian cancer screening (PsyFOCS) is underway in partnership with the UK Familial Ovarian Cancer Screening Study (UK FOCSS Phase 2). One of the aims of PsyFOCS is to examine factors associated with withdrawal from the UK FOCSS prior to the onset of 4-monthly screening. METHOD: 1999 of 3224 women completed a baseline questionnaire. 110 (5.5%) women withdrew from screening prior to their first routine Phase 2 screen, of which 73 (66.4% of withdrawals) had withdrawn because they had undergone removal of their ovaries and fallopian tubes (withdrawn group). The comparison group consisted of 1868 women who remained on screening. The baseline questionnaire included measures of cancer-specific distress, anxiety, depression and illness perceptions. RESULTS: Logistic regression analysis indicated that having had prior annual (Phase 1) screening (OR=13.34, p<.01), past experience of further tests (OR=2.37, p<.01) and greater cancer-specific distress (OR=1.38, p<.01) were associated with withdrawal for surgery. Belief in ageing as a cause of ovarian cancer was also associated with withdrawal (OR=1.32, p=.05). CONCLUSION: These cross-sectional data suggest that withdrawal from familial ovarian cancer screening may be influenced by both clinical and psychological factors. These may reflect women's experience of the drawbacks of screening and increased concern about ovarian cancer risk, as well as having opportunities to consider surgery as an alternative risk management strategy whilst using screening as an interim measure.